2010
DOI: 10.1121/1.3505123
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of distortion-product otoacoustic emissions after a 2-kHz monaural sound-exposure in humans: Effects on fine structures

Abstract: A better understanding of the vulnerability of the fine structures of distortion-product otoacoustic emissions (DPOAEs) after acoustic overexposure may improve the knowledge about DPOAE generation, cochlear damage, and lead to more efficient diagnostic tools. It is studied whether the DPOAE fine structures of 16 normal-hearing human subjects are systematically affected after a moderate monaural sound-exposure of 10 min to a 2-kHz tone normalized to an exposure level L(EX,8h) of 80 dBA. DPOAEs were measured bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Consistent with Krause et al (2013), Stromberg et al (2016) did not find significant reduction in measurable hearing thresholds after exposure but found a reduction in DPOAE amplitude over a larger range of frequencies. Stromberg et al (2016) found a DPOAE reduction (2.1 dB) following cVEMP evaluation that was equivalent to half the reduction caused by exposure to the maximally allowed occupational noise for an 8-hr work day as reported by Reuter et al (2007) and Aranda de Toro et al (2010). Most recently, Mattingly et al (2015) report a case study of sudden permanent bilateral sensorineural hearing loss after cVEMP and oVEMP testing with stimulation intensities ranging between 128 and 135 dB pSPL.…”
mentioning
confidence: 78%
“…Consistent with Krause et al (2013), Stromberg et al (2016) did not find significant reduction in measurable hearing thresholds after exposure but found a reduction in DPOAE amplitude over a larger range of frequencies. Stromberg et al (2016) found a DPOAE reduction (2.1 dB) following cVEMP evaluation that was equivalent to half the reduction caused by exposure to the maximally allowed occupational noise for an 8-hr work day as reported by Reuter et al (2007) and Aranda de Toro et al (2010). Most recently, Mattingly et al (2015) report a case study of sudden permanent bilateral sensorineural hearing loss after cVEMP and oVEMP testing with stimulation intensities ranging between 128 and 135 dB pSPL.…”
mentioning
confidence: 78%